The art of the network : strategic interaction and patronage in Renaissance Florence - McLean, Paul Douglas, 1962- (Politics, history, and culture., 2007)
A sociological study of networking that explores the relationship between networks and agency and that analyzes a rich historical antecedent of contemporary networking and the concept of self that accompanies it.